2017
DOI: 10.1002/anie.201700190
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective γ‐Selective Additions of 2‐Allylazaarenes to Activated Ketones

Abstract: Reported herein is the first example of 2-allylazaarenes in asymmetric catalysis. Highly γ-selective allylation was demonstrated for activated ketones, including isatins and trifluoromethyl ketones. In the presence of either an amino-acid-based tertiary amine or quaternary ammonium salt catalyst, two series of tertiary hydroxy-containing moieties were installed at the remote δ-position of azaarenes in good chemical yields, excellent enantioselectivities, and E/Z ratios. The success of current γ-selective react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 68 publications
0
24
0
Order By: Relevance
“…Next, the screening of polar aprotic solvents such as EtOAc, THF and 1,4-dioxane revealed that THF solvent was superior than the other two solvents as it gave 68% yield of the product. The use of chlorinated solvents such as DCE and TCE and non-polar solvent such as toluene did not increase the product yield (entries [8][9][10]. When PEG 200 was used as the solvent, it rendered the product in 77% yield (entry 11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the screening of polar aprotic solvents such as EtOAc, THF and 1,4-dioxane revealed that THF solvent was superior than the other two solvents as it gave 68% yield of the product. The use of chlorinated solvents such as DCE and TCE and non-polar solvent such as toluene did not increase the product yield (entries [8][9][10]. When PEG 200 was used as the solvent, it rendered the product in 77% yield (entry 11).…”
Section: Resultsmentioning
confidence: 99%
“…[3] However, shortcomings, such as the use of pyrophoric base and the need of cryogenic temperature, associated with this approach were first overcome by Huang and co-workers by treating 2-methylazaarenes with N-sulfonyl aldimines using Pd(OAc) 2 /1,10-phen catalyst (Scheme 1b). [4] Afterwards, both Brønsted acid [5] and Lewis acid [6][7] catalyzed transformations, as well as transition metalfree [8] and asymmetric [9] approaches have been reported by varying the electrophiles (Scheme 1c). Although these transformations have many benefits, they require the use of corrosive Brønsted acid and homogeneous Lewis acid catalysts and external ligand, and most of the reports were not focused on the recovery of the catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction is catalyzed by chiral aminoacid-based tertiary amines (AATA) XII or aminoacid-based quaternary ammonium salt (AAQA) XI and the addition takes place at the γ-position of the allyl group leading to δ-tertiary hydroxy-containing compounds. [22] The reaction between 2-allyl azaarenes 110 and aryltrifluoromethyl ketones 111 leads to compound 112 in high yields, ranging from 71 to 96%, with ee from 86 to 99%. In this case the reaction requires the presence of 2 equiv.…”
Section: Unsaturated Alkyl Azaarenesmentioning
confidence: 99%
“…119~121 ℃ (Lit. [12] (d,J=6.4 Hz,2H), 3.52 (s,1H),4.87 (d,J=6.4 Hz,1H),7.45~7.47 (m,3H),7.68 (d,J=4.4 Hz, 2H); 13 C NMR (100 MHz, CDCl 3 ) δ: 173. 4, 160.2, 134.6, 129.5, 129.1, 128.7, 125.9, 124.9 (q, J C -F =285.5 Hz), 79.4 (q, J C -F =27.7 Hz), 37.3, 19.8, 13.2, 11.0; 19 F NMR (376 MHz, CDCl 3 ) δ: -76.73 (s, 3F), -73.99;IR (KBr) ν: 3420, 2979, 2939, 1599, 1514, 1449, 1355, 1301, 1203, 1149, 1070, 1017 (s,1H),4.83 (dd,J=13.6,6.8 Hz,1H),7.15 (t,J=8.4 Hz,2H),7.65 (t,J=4.4 Hz, 2H); 13 C NMR (100 MHz, CDCl 3 ) δ: 37.3, 19.8, 13.2, 11.0; 19 F NMR (376 MHz, CDCl 3 ) δ: -76.95 (s, 3F), -74.32, -112.45 (s, 1F), -112.07;IR (KBr) ν: 3446, 2978, 2943, 1599, 1509, 1431, 1367, 1262, 1205, 1156, 1016 (d,…”
Section: 2mentioning
confidence: 99%